Poluição por microplásticos : distribuição nos ambientes aquáticos no Pantanal - Faria, Érika de (2022)
Microplastics represent an emerging global threat to freshwater ecosystems. Studies regarding their presence in floodplains are still incipient. Microplastics in the Pantanal’s affluent and floodplains were sampled close to their potential urban sources and in the Pantanal lowlands. A plankton net (68 μm mesh size), with a 150 ml collection flask was used for sampling. The flask content was filtered over a 0.45μm Whatman paper, 47 mm in diameter, and examined under a stereomicroscope at 45X to identify and count microplastics (expressed as x100L-1 ). Visual determination was then confirmed by Raman spectrometry. . Fibers, fragments, pellets, and XPS (closed-cell extruded polystyrene foam) particles represented respectively 50%, 19%, 22%, and 9% of the total microplastics. Microplastics concentrations were higher in the urban tributaries (19.9±5.8 x100L-1 ) than in the Pantanal lowlands (4.5±2.5 x100L-1 ). Fibers were the most important fraction, followed by fragments. Fibers, fragments, and films represented respectively 67.8%, 27.8%, and 4.4%, of the total microplastics. Surprisingly, synthetic blue fibers of non-identified composition, which Raman spectra suggest are composed of PbO, Cu2FeSn3S8, or LiNbO3, account for 51% of the 730 microplastics found. Other identified polymers include PP (18.2%), PET (16.9%), PVC (5.1%), PVA (4.4%), and LDPE (4.4%). The blue fiber, PP and PET were found at all sample locations. Microplastics concentrations varied from 2.25±0.47 x/100L to 4.75±1.52 x/100L across the sampling sites. Average concentrations varied in time from 3.40±1.13 to 4.33±1.81 x/100L. The median concentrations (1.3 x/100L) in lentic environments were significantly lower than in the lotic ones (1.7 x/100L). Urban human activities are a potential source of microplastics as the concentrations of these increased significantly with the population of nearest human agglomeration. These results indicate a widespread contamination of the Pantanal waters by microplastics. Furthermore, a microsynthetic of indeterminate composition possibly associated with e-waste is present everywhere in the Pantanal and more research is urgently needed to determine its composition and sources Contamination by micropolymers and other microsynthetics is likely to impact the Pantanal biota and eventually humans living in these floodplains.